2016
DOI: 10.1177/0271678x15616980
|View full text |Cite
|
Sign up to set email alerts
|

Video training and certification program improves reliability of postischemic neurologic deficit measurement in the rat

Abstract: Scoring systems are used to measure behavioral deficits in stroke research. Video-assisted training is used to standardize stroke-related neurologic deficit scoring in humans. We hypothesized that a video-assisted training and certification program can improve inter-rater reliability in assessing neurologic function after middle cerebral artery occlusion in rats. Three expert raters scored neurologic deficits in post-middle cerebral artery occlusion rats using three published systems having different complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To extensively evaluate functional outcome at this early recovery interval after stroke, we used a 48-point scoring system that consists of 14 categories, and includes several behavioral tests. 19 After testing, ATF6-KI mice showed better neurologic function (Figure 3(c); p = 0.0002). Together, our findings demonstrated that the ATF6 UPR branch plays an important role in protection of the brain from ischemic damage and in restoration of neurologic function impaired by ischemia.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…To extensively evaluate functional outcome at this early recovery interval after stroke, we used a 48-point scoring system that consists of 14 categories, and includes several behavioral tests. 19 After testing, ATF6-KI mice showed better neurologic function (Figure 3(c); p = 0.0002). Together, our findings demonstrated that the ATF6 UPR branch plays an important role in protection of the brain from ischemic damage and in restoration of neurologic function impaired by ischemia.…”
Section: Resultsmentioning
confidence: 93%
“…Neurologic assessment was performed at 24 h post MCAO using a 48-point scoring system as recently detailed. 19 Before evaluation, an observer who was blind to the genotype of the animals completed the video-assisted training and certification program in order to standardize the scoring process. This comprehensive scoring system evaluates general status (spontaneous activity, body symmetry, gait; 0–12), simple motor deficit (forelimb asymmetry, circling, hind limb placement; 0–14), complex motor deficit (vertical screen climbing, beam walking; 0–8), and sensory deficit (hind limb, trunk, vibrissae, and face touch; 0–14).…”
Section: Methodsmentioning
confidence: 99%
“…They studied the reliability of experienced oculomotor researchers at a single point in time, without any rater training or consensus discussions. There is a very large literature on the beneficial effects of rater training (Abaza & Ross, 2009;Abbo, Okello, & Nakku, 2013;Alcott, Swann, & Grafham, 1999;Angkaw, Tran, & Haaga, 2006;Bank et al, 2002;Buijze, Guitton, van Dijk, Ring, & the Science of Variation Group, 2012;Chan & Yiu, 2002;Chapman et al, 2016;Cusick, Vasquez, Knowles, & Wallen, 2005;Degenhardt, Snider, Snider, & Johnson, 2005;Haj-Ali & Feil, 2006;Istriana et al, 2013;Iwarsson & Reinholt Petersen, 2012;Lievens, 2001;Lou et al, 2014;Lundh, Kowalski, Sundberg, & Landen, 2012;Magnan & Maklebust, 2009;Mist, Ritenbaugh, & Aickin, 2009;Rosen et al, 2008;Sattler, McKnight, Naney, & Mathis, 2015;Schredl, Burchert, & Gabatin, 2004;Solah et al, 2015;Staelens et al, 2014;Store-Valen et al, 2015;Taninishi et al, 2016). There is also a literature on the beneficial effects of having consensus discussions and employing consensus guidelines (Beerbaum et al, 2009;Degenhardt et al, 2005;Foppen, van der Schaaf, Beek, Verkooijen, & Fischer, 2016;Iwarsson & Reinholt Petersen, 2012;Meade et al, 2000;Weinstock et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For neurological scores, a 48-point scoring system was used to evaluate neurological deficits, as detailed previously (Taninishi et al, 2016;Wang Y. C. et al, 2020). Briefly, this comprehensive scoring system assesses general status, motor deficits, and sensory deficits.…”
Section: Neurological Scores and Rota Rod Testmentioning
confidence: 99%